Single-center experience in hybrid approach for subclavian vein effort thrombosis - Maksym Katelenets, MD; Victor Ginzburg, MD; Anatoly Leytzin, MD; Dmitry Shepovalov, MD; Abu Kush Nahel, MD; George Greenberg, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Objective: Effort thrombosis of the subclavian vein (SCV) is one of the forms of deep vein thrombosis in the upper extremity and plays the leading role in venous thoracic outlet syndrome. This condition affects predominantly young and active people and can lead to extremity functional deterioration and long-term consequences. Despite the apparent clinical importance, no consensus or accepted protocol regarding optimal treatment exists. The main aim of this study was to present our local treatment protocol and to assess its effectiveness, safety, and functional impact. Methods: We conducted a single-center retrospective analysis of 27 patients hospitalized and treated in our department with effort SCV thrombosis from September 2005 to December 2022. The median length of follow-up was 92 months (range, 6-140 months). Evaluation of early and late stent patency and the assessment of chronic venous insufficiency, using the Villalta score and arm functional status using the QuickDASH-9 questionnaire, were performed. Results: Of these 27 patients, 23 were treated using catheter-directed thrombolysis, first rib resection with subsequent endovascular repair of the SCV using a self-expanding stent. A total of 18 patients were assessed for vein patency and showed an early patency of 94.4% and a late patency of 83.3%. Four stents were found to be occluded. None of the treated patients has developed clinically significant chronic venous insufficiency, and the median Villalta score was 1 point. The median functional status of the arm measured by the QuickDASH-9 questionnaire was 2.75. Conclusions: First rib resection is an integral part of the treatment approach and is prominent in releasing chronic bony compression of the SCV. Subsequent endovascular repair achieves unaffected prograde flow and excellent long-term vein patency. Despite surgical aggressiveness, the current approach shows promising results in the context of the safety and functional status of the affected limb.